2023
DOI: 10.1007/s10578-023-01501-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Kessler Psychological Distress Scale in a Sample of Adolescents from Ecuador

Abstract: The Kessler psychological distress scale is a useful tool for identifying possible psychological problems and has been widely used in research and health services. Unfortunately, its application in various populations has not always been psychometrically supported. For this reason, the present study investigated the psychometric properties of its Spanish version in adolescents, verifying its factorial structure, measurement invariance by gender, internal consistency and the discrimination and difficulty parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…The fifth item on the Kessler-6 (‘ feeling like everything was an effort’ ) revealed low item-rest correlation and, if removed, would result in a five-item measure of psychological distress with improved, although still low, internal consistency ( = 0.594). This item has displayed low loadings and weak item-rest correlations in a previous validation study of the 10-item Kessler scale in Ecuador (Larzabal-Fernandez et al, 2023 ).…”
Section: Resultsmentioning
confidence: 82%
“…The fifth item on the Kessler-6 (‘ feeling like everything was an effort’ ) revealed low item-rest correlation and, if removed, would result in a five-item measure of psychological distress with improved, although still low, internal consistency ( = 0.594). This item has displayed low loadings and weak item-rest correlations in a previous validation study of the 10-item Kessler scale in Ecuador (Larzabal-Fernandez et al, 2023 ).…”
Section: Resultsmentioning
confidence: 82%
“…Currently, the gender presents scientific, social, and cultural importance, with debates about the psychic response in various attributes that sometimes present prejudices and inaccuracies (Upchurch, 2020) and feed narra-tives loaded with ideology that in this aspect science and psychology should help to clear with evidence But in the case of the sciences, preliminary findings of gender differences without precise and reliable instruments are questionable, since they do not guarantee that the calibration represents equality of measurement between the groups. In this sense, is common in multi-group research that, when conducting comparative analyses, no prior verification of the ME of a measure is carried out in order to estimate inter-group discrepancies because, if they exist, it is unlikely to determine whether they are due to divergences in the interpretation of the items in the structure of the scale or to the characteristics of the groups themselves (Asparouhov & Muthén, 2014;Larzabal-Fernandez et al, 2023;Moreta-Herrera et al, 2021;Van de Schoot et al, 2015). The inability to account for the exact origin of the difference between groups leads to bias in the estimation of the final conclusions.…”
Section: Pil-sf: Implications and Psychometric Needsmentioning
confidence: 99%
“…(Dowdy et al, 2018 ). On the other hand, K10 includes two sets of items: anxiety, which includes items like Fatigued, Nervous, Very nervous, Restless, Very restless, and No energy; and depression, which includes items like Hopeless, Sad, Very sad, and Useless (Larzabal-Fernandez et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The K10 was not specifically designed for children and adolescents, but K10 and its 6-item version (K6) have been used with adolescents in various studies and demonstrated quite good psychometric properties in diverse settings including China, Indonesia, USA, and Ecuador (Chan & Fung, 2014 ; Larzabal-Fernandez et al, 2023 ; Mewton et al., 2016 ; Tran et al, 2019 ). However, one of the most recent studies (Larzabal-Fernandez et al, 2023 ), points out that the evidence of validity for K10 in the adolescent population is quite limited and controversial and is reduced to two studies, both using the 6-item version (K6) (Mewton et al, 2016 ; Tran et al, 2019 ) and that they had not been able to find studies investigating the psychometric properties of the K10 in adolescents. Furthermore, in the study with Ecuadorian adolescents, they concluded that the 9-item version of the K10 was the most appropriate for this population.…”
Section: Introductionmentioning
confidence: 99%